1987
DOI: 10.1128/jb.169.5.2294-2297.1987
|View full text |Cite
|
Sign up to set email alerts
|

Response to temperature shifts of expression of the amp gene on pBR322 in Escherichia coli K-12

Abstract: Synthesis of beta-lactamase, the product of the amp gene on pBR322, in Escherichia coli K-12 was reversibly repressed with a shift-up of the growth temperature from 30 to 42 degrees C. The temperature shift, however, did not affect the level of mRNA encoding beta-lactamase, which suggested the involvement of translational control.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
23
0

Year Published

1987
1987
2007
2007

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 19 publications
(24 citation statements)
references
References 25 publications
1
23
0
Order By: Relevance
“…However, they also concluded that this regulation was independent of the rpoH allele (26). Kuriki showed that the heat shock-induced suppression of ,-lactamase synthesis was regulated by the initiation of translation and depended on a short nucleotide sequence containing the Shine-Dalgarno sequence and the ATG start codon of ,-lactamase (16,17).In contrast, there is evidence from yeast cells that mRNA degradation can affect the suppression of the synthesis of non-heat shock proteins during the heat shock response. A temperature shift from 23 to 36°C resulted in a decrease in the synthesis of ribosomal proteins, with a corresponding rapid decrease in the cellular levels of ribosomal protein mRNAs (14).…”
mentioning
confidence: 95%
“…However, they also concluded that this regulation was independent of the rpoH allele (26). Kuriki showed that the heat shock-induced suppression of ,-lactamase synthesis was regulated by the initiation of translation and depended on a short nucleotide sequence containing the Shine-Dalgarno sequence and the ATG start codon of ,-lactamase (16,17).In contrast, there is evidence from yeast cells that mRNA degradation can affect the suppression of the synthesis of non-heat shock proteins during the heat shock response. A temperature shift from 23 to 36°C resulted in a decrease in the synthesis of ribosomal proteins, with a corresponding rapid decrease in the cellular levels of ribosomal protein mRNAs (14).…”
mentioning
confidence: 95%
“…Another possibility is that the amp promoter is occluded by the ompF promoter and thus has no influence on the level of P-galactosidase encoded by pNO5 and pNO18. When 3-galactosidase synthesis was initiated from the amp start codon, i.e., that taking place in cells harboring pNO5 or pNO18, the P-galactosidase level in cells growing at 42°C was only about 25% of that in cells growing at 30°C, as in the case of P-lactamase synthesis in cells carrying pBR322 (4). In contrast, cells harboring pNO2 produced about 1.2-fold more j-galactosidase at 42 than at 300C.…”
Section: Methodsmentioning
confidence: 92%
“…Thus, in E. coli as in eucaryotic cells (12,14), heat shock leads not only to transient overproduction of a specific set of (heat shock) proteins (10,11), but also to transient repression of the synthesis of certain proteins (4,7). Since the synthesis of 3-lactamase mRNA is not repressed by temperature shift-up (4), it is thought that the repression of ,B-lactamase synthesis occurs at the translation level. In fact, the translation of 1-lactamase mRNA in vitro has been shown to be specifically repressed at higher temperature, such as 45°C (unpublished results).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…It was concluded that the temperature shift-up repressed P-lactamase synthesis at the translational level (4), in contrast to the characteristics of heat shock proteins, the syntheses of which are regulated by sigma 32 as the rpoH gene product at the transcriptional step (2,6,8,(12)(13)(14)(15). The repression of 1-lactamase synthesis by heat shock seems to be an example of the heat shock response of E. coli and should be useful for the study of the regulation of gene expression at the translational level in E. coli.…”
mentioning
confidence: 99%